Leveraging New Technology for Data-Driven Risk Mitigation and Management : Selected Examples and Summaries - Khokhar, Tariq (World Bank, Washington, DC, 2013)
This report asserts that in the last decade, technologies have emerged that make the collection, analysis, and distribution of data faster, cheaper, and possible in places where it wasn’t before, and novel applications that combine these technologies and the data they produce, along with new analytical techniques, change the mitigation, management, and evaluation of responses to risk. Individuals can leverage the same technologies to take informed risks and pursue opportunities. The timeliness of data and actionable information remains the biggest advantage for risk mitigation and management, and timely information delivered quickly can also improve the efficiency of markets and allow individuals to spot and pursue opportunities. However, while the benefits remain clear, and can assist in preparing for and dealing with risk, these technologies do have drawbacks and some can pose some risks to their users. Organizations should be aware of these before deploying these tools and using the data they produce.